If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (-9y) + (-10x) + y = 0 Reorder the terms: 3x + (-10x) + (-9y) + y = 0 Combine like terms: 3x + (-10x) = -7x -7x + (-9y) + y = 0 Combine like terms: (-9y) + y = -8y -7x + -8y = 0 Solving -7x + -8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8y' to each side of the equation. -7x + -8y + 8y = 0 + 8y Combine like terms: -8y + 8y = 0 -7x + 0 = 0 + 8y -7x = 0 + 8y Remove the zero: -7x = 8y Divide each side by '-7'. x = -1.142857143y Simplifying x = -1.142857143y
| 230b-110=97 | | 8a^3-5a^3= | | 14x-30-10x-9-3x=19-4x+142 | | 7x+4=-3x-16 | | 4x+2.5y=10 | | 5x^2+9x-3=0 | | 4x+(-x)-y+y=-2+(-4) | | 9x+1-(3x+7)=24 | | 20x-36+2x=3x-17 | | 5x=52 | | 3a+4y=2b | | 3(-3x+1)=21 | | 9x-6=3x+12 | | -.11(x-27)+.33(x+3)=x-3 | | 6x-4=10-x | | 8(a+x)=b-a+3x | | x^2-9=6x-2 | | 7x=5x-24 | | 4a-3=2(a+1)+9a+4 | | 2x+5(-3x+1)=-3(-3x+1) | | x=(16*16*16)-(14*14*14) | | =(16*16*16)-(14*14*14) | | -20-2r=2r+4 | | =(16*16*16) | | 17-4x=19-5x | | 0.6+0.004+0.07+0.0098= | | 8x-5=-3x+20 | | 54-5x=13x+20 | | 2(12y+15)=y+(31-5y) | | 6x+10=98+5x | | 4-(12y+15)=y+(31-5y) | | 2x-130=16 |